Square wave cathodic stripping voltammetric technique for determination of aflatoxin B1 in ground nut sample - Yaacob, Mohamad Hadzi; Mohd. Yusoff, Abd. Rahim; Ahmad, Rahmalan (The Malaysian Analytical Sciences Society, 2008)

(untitled)
An electroanalytical method has been developed for the detection and determination of 2,3,6a,9a-tetrahydro-4-methoxycyclo penta[c] furo[3’,2’:4,5] furo [2,3-h][l] benzopyran-1,11-dione (aflatoxin B1, AFB1) by a square wave cathodic stripping voltammetric (SWSV) technique on a hanging mercury drop electrode (HMDE) in aqueous solution with Britton-Robinson Buffer (BRB) at pH 9.0 as the supporting electrolyte. Effect of instrumental parameters such as accumulation potential (Eacc), accumulation time (tacc), scan rate (v), square wave frequency, step potential and pulse amplitude were examined. The best condition were found to be Eacc of -0.8 V, tacc of 100 s, v of 3750 mVs-1, frequency of 125 Hz, voltage step of 30 mV and pulse amplitude of 50 mV. Calibration curve was linear in the range of 0.01 to 0.15 uM with a detection limit of 0.125 x 10-8 M. Relative standard deviation for a replicate measurement of AFB1 (n = 5) with a concentration of 0.01 ?M was 0.83% with a peak potential of -1.30 V (against Ag/AgCl). The recovery values obtained in spiked ground nut elute sample were 94.00 ± 0.67 % for 3.0 ppb, 91.22 ± 1.56 % for 9 ppb and 92.56 ± 2.00 % for 15.0 ppb of AFB1. The method was applied for the determination of the AFB1 in ground nut samples after extraction and clean-up steps. The results were compared with that obtained by high performance liquid chromatography (HPLC) technique.